Delay analysis framework for residential building construction in Abu Dhabi, United Arab Emirates - Mohamed, Shahnaz Ali Abdalla (2023)
The delay analysis framework consolidates diverse techniques and methods to achieve automated schedule analysis and damage calculation. The aim of this study is to develop a delay analysis framework to improve the claim processes for residential construction projects in Abu Dhabi (UAE). Previous research shows that 50% of the construction projects in the UAE encountered delays and were not completed on time. Delay Analysis Method (DAM) has been used in the construction industry to analyse the causes and effects of delays and plays a significant part of the claim process. The objectives of the study are to identify the current practices of Delay Analysis Method for residential building construction claims in the UAE, analyse the challenges of this method and determine the selection practices for the claims. The focus of the study is to develop an appropriate delay analysis framework in order to improve claim processes in residential construction projects. The research involved five case studies including one community villa project and four residential building projects in Abu Dhabi, UAE. The research instruments used were interviews and surveys involving 200 project stakeholders (consultants and contractors) who are working in residential construction projects in Abu Dhabi, UAE. Thematic analysis was applied to analyse the interviews with the consultants and the data was analysed using NVivo software. Meanwhile, the quantitative data from the survey was analysed using descriptive statistical analysis. The research found that most of the participants (179=83.3%) usually used Windows/Time Impact Analysis. The participants indicated that lack of adequate project information is a consistent obstacle. Majority of them (168=85.28%) indicated that contractual requirements are a strong factor for selecting an effective delay analysis method/technique. To develop the delay analysis framework, most of them revealed that using a suitable Delay Analysis Method and skilled delay analysts will save time, cost and effort. The findings from this study contribute to the body of knowledge as the framework produced is pertinent for future studies that explore ways to overcome the obstacles of delay analysis in order to improve claim processes for a wide range of projects in Abu Dhabi.